EXPERTISE IN TECHNICAL TERMS - AN IMPORTANT STAGE IN THE DEVELOPMENT AND MANUFACTURE OF PRODUCTS FOR RAILWAY ROLLING STOCK - Myamlin, S. V.; Dubynets, L. V.; Vyslohuzov, V. T.; Duhanov, O. H. (Science and Transport Progress, 2006)
An important stage of development and manufacture of the products and parts for rolling stock is a quality expertise of draft specifications at a stage of their development. The article enlists the component parts of the specifications project, the estimation criteria of the project conformity to the existing norms and legal documents, the main characteristic drawbacks of projects and a mechanism of their removal.